Effects of Cryoprotective Medium Composition, Dilution Ratio, and Freezing Rates on Spotted Halibut (Verasper variegatus) Sperm Cryopreservation - Zidni, Irfan (Animals (Basel), 2020)
SIMPLE SUMMARY: The spotted halibut, Verasper variegatus, is a popular fish species occurring naturally in the East China Sea and coastal areas of Korea and Japan. However, when reared in captivity, male and female spotted halibut do not usually mature synchronously. Maintaining production of this commercial fish in hatcheries through sperm cryopreservation is important. This study investigated the effect of several factors for successful cryopreservation of fish sperm including cryoprotective agents (CPAs), diluents, dilution ratios (Milt: CPA + diluents), and freezing rates. The observed factors significantly affected movable sperm ratio (MSR), sperm activity index (SAI), survival rate, and DNA damage after cryopreservation. In the present study, the mixture of 15% dimethyl sulfoxide (DMSO) + 300 mM sucrose with a dilution ratio lower than 1:2 and a freezing rate slower than −5 °C/min provided the best treatment and reduced DNA damage. These results can contribute to the development of a cryopreservation protocol for spotted halibut hatcheries. ABSTRACT: The spotted halibut is species that has a high potential market value in Korea, but the supply of seed is unstable because of the limited milt production of males. The objective of this research was to explore different aspects, such as CPAs, diluents, dilution ratio, and freezing rates, to develop an optimal sperm cryopreservation. The parameters assessed were movable sperm ratio, sperm activity index, survival rate, and DNA damage. The CPAs tested in this research were propylene glycol, dimethyl sulfoxide (DMSO), methanol, ethylene glycol, and glycerol. Different diluents, including 300 mM sucrose, 300 mM glucose, Stain’s solution, and Ringer’s solution, were investigated. The previous experiment showed that the optimal CPA for cryopreservation was DMSO with a concentration of 15% with 300 mM as diluent. To determine the effect of the dilution ratio, sperm was diluted to 1:1, 1:2, 1:10, 1:100, and 1:1000 with 300 mM sucrose containing DMSO at a final concentration of 15%. Lastly, the optimal freezing rate of the sperm was evaluated with four different freezing rates (−1, −5, −10, and −20 °C/min). Post-thaw sperm motility was higher with a dilution ratio lower than 1:2, and the freezing rate was less than −5 °C/min. In conclusion, these findings represent the development of a cryopreservation protocol for spotted halibut.